ChemInform Abstract: Visible‐Light‐Mediated Fluoroalkylation of Isocyanides with Ethyl Bromofluoroacetates: Unified Synthesis of Mono‐ and Difluoromethylated Phenanthridine Derivatives. Issue 48 (2nd December 2014) - Sun, Xiaoyang; Yu, Shouyun
Abstract A visible‐light promoted alkylation, followed by decarboxylation starting from biphenyl isocyanides with acetates (II) or (V) gives access to the title species (IV) and (VII) in a stepwise or a one‐pot manner.